2018
DOI: 10.9734/jeai/2018/39621
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Economic Risk of Programmed Pruning Cycle in Arabic Coffee

Abstract: Coffee crop represents a great economic importance in Brazil, in which Arabica coffee represents a great part of the national production. However, the average yield of Arabica coffee is low, which reduces the profitability of the activity. Pruning systems can regain vigor and increase productivity. The system most adopted by coffee farmers is "recepa" (cutting off the orthotropic branch at 0.8 m above ground), which has not resulted in efficient reinvigoration. It is believed that the implementation of new sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…At present, the most effective pruning system in Conilon coffee is the cycle pruning programmed (CPP), which consists of changing the plant architecture so as to maintain 12,000 to 15,000 orthotropic branches per hectare (Verdin-Filho et al, 2016) and eliminating the plagiotropic branches which have already attained 70% of their production capacity. The cycle pruning programmed has several advantages when compared to traditional systems, e.g., increased average yield and standardization of the crop; reduced total man labor in the long term, as CPP is performed at every four or five cycles; greater ease in thinning and cultivation practices; greater uniformity of flowering and fruit maturation; greater ease in pest and disease control; higher production stability per cycle; and non-occurrence of "zero harvest", ensuring yearly production (Gathaara;Kiara, 1984;Verdin-Filho et al, 2014;Verdin-Filho et al, 2016;Baitelle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the most effective pruning system in Conilon coffee is the cycle pruning programmed (CPP), which consists of changing the plant architecture so as to maintain 12,000 to 15,000 orthotropic branches per hectare (Verdin-Filho et al, 2016) and eliminating the plagiotropic branches which have already attained 70% of their production capacity. The cycle pruning programmed has several advantages when compared to traditional systems, e.g., increased average yield and standardization of the crop; reduced total man labor in the long term, as CPP is performed at every four or five cycles; greater ease in thinning and cultivation practices; greater uniformity of flowering and fruit maturation; greater ease in pest and disease control; higher production stability per cycle; and non-occurrence of "zero harvest", ensuring yearly production (Gathaara;Kiara, 1984;Verdin-Filho et al, 2014;Verdin-Filho et al, 2016;Baitelle et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PPAC may reduce mortality in the plants subjected to pruning, increase their longevity and yield due to reinvigoration as well as reduce yield bienniality. Baitelle et al (2018) studied the use of PPAC and concluded that, in the long term, it is more economically viable than the recepa for mountain coffee growers who do not adopt mechanization. They concluded that at a minimum attractiveness rate of 12%, the implementation of scheduled pruning is feasible as it generates a TRI of 15.30%, about 3.3 percentage points higher than the minimum attractiveness rate.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the economic analysis, except for the sensors, all prices of inputs used were collected from the study region. The price per kg of corn (US$ kg -1 ) was based on the average local price from the last five years (2014( , 2016( , and 2018, which is established by the Central of Supply of Minas Gerais (Ceasa -Minas). It should be mentioned that only five years were used due to the lack of data from previous years.…”
Section: Data Sourcementioning
confidence: 99%
“…This distribution has as input parameters: the minimum, the modal (most likely) or average value of the variable under study, and the maximum value. As mentioned before, the use of the triangular distribution represents an alternative when sufficient historical data for a particular variable is not available (Baitelle et al, 2018).…”
Section: Economic Feasibility Analysis Under Risky Conditionsmentioning
confidence: 99%
“…Plant growth regulators (PGR) in low concentrations can encourage, inhibit, or modify growth and development both in quantity and quality. PGR improves the absorption of nutrients by plants [9], PGR makes it possible to exploit the production potential of plants. In addition, PGR serves to accelerate the response of plants to the environment [10].…”
Section: Introductionmentioning
confidence: 99%